Antimicrobial Peptides Act-6 and Act 8-20 Derived from Scarabaeidae Cecropins Exhibit Differential Antifungal Activity - Melissa Rodríguez; Lily J. Toro; Carolina Firacative; Beatriz L. Gómez; Bruno Rivas-Santiago; David Andreu; Jhon C. Castaño; German A. Téllez; Julián E. Muñoz (Journal of Fungi, 2025)
The number of fungal infections is steadily increasing, with considerable morbidity and mortality. Additionally, antifungal resistance is a growing concern, highlighting the need to develop new treatment options. One alternative is the use of antimicrobial peptides (AMPs). The aim of this study was to assess the in vitro and in vivo antifungal activity of designed short AMPs, Act-6 and Act 8-20, derived from cecropin transcripts of beetles from the family Scarabaeidae, against eight reference strains of the pathogenic yeasts Candida and Cryptococcus. We also evaluated the effect of these modified AMPs on the biofilm, morphogenesis, and cell morphology of Candida albicans, as well as the in vivo activity via a murine model of disseminated candidiasis. The AMPs herein analyzed exhibit differential antifungal activity against the yeasts assessed, and inhibit biofilm, hyphae, and pseudohyphae formation with morphological alterations in C. albicans. Moreover, the fungal load in mice treated with these AMPs significantly decreased. Altogether, our results suggest that Act-6 and Act 8-20 are promising antifungal molecules to control mycoses.